2013
DOI: 10.1038/hdy.2013.117
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic selection factors induce a continuous population divergence in a polymorphism

Abstract: Understanding the relative importance of selection and stochastic factors in population divergence of adaptive traits is a classical topic in evolutionary biology. However, it is difficult to separate these factors and detect the effects of selection when two or more contrasting selective factors are simultaneously acting on a single locus. In the damselfly Ischnura senegalensis, females exhibit color dimorphism and morph frequencies change geographically. We here evaluated the role of selection and stochastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 43 publications
4
22
1
Order By: Relevance
“…Molecular work across 22 European I. elegans populations demonstrates low genetic differentiation (mean F ST = 0.06), presumably because of efficient dispersal (Wellenreuther et al 2011) (Table 1). Similar levels of genetic differentiation were detected across 30 populations of I. senegalensis in Japan (F ST = 0.10), another wide ranging species of the Palearctic 'elegans' clade (Takahashi et al 2013). Even species with more restricted distributions show similar levels of genetic differentiation (data derived from four populations of each species covering their distribution: I. graellsii F ST = 0.03; I. genei F ST = 0.13; and I. saharensis F ST = 0.09, R.…”
Section: Conserved Ranges and Niche Overlap In Ischnurasupporting
confidence: 60%
“…Molecular work across 22 European I. elegans populations demonstrates low genetic differentiation (mean F ST = 0.06), presumably because of efficient dispersal (Wellenreuther et al 2011) (Table 1). Similar levels of genetic differentiation were detected across 30 populations of I. senegalensis in Japan (F ST = 0.10), another wide ranging species of the Palearctic 'elegans' clade (Takahashi et al 2013). Even species with more restricted distributions show similar levels of genetic differentiation (data derived from four populations of each species covering their distribution: I. graellsii F ST = 0.03; I. genei F ST = 0.13; and I. saharensis F ST = 0.09, R.…”
Section: Conserved Ranges and Niche Overlap In Ischnurasupporting
confidence: 60%
“…Here we describe the ecological assumptions underlying this model and present the mathematical model in more detail. We derive predictions for equilibrium morph frequency, population density and the stability of populations by considering the variation in model parameters caused by a morph-specific geographic cline in female fitness 22,23 . Female colour morph diversity within a population (D) was calculated using the Shannon species diversity index 36 …”
Section: Discussionmentioning
confidence: 99%
“…In natural populations, the female morph frequency exhibits clinal variation, which is generated by the difference in potential fecundity between female morphs in each population 22,23 . Previous studies have shown that the potential fecundity of the different female morphs of I. senegalensis changes with latitude 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations